STUDY ON PHENOTYPIC AND GENOTYPIC DETECTION OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) AND DISTRIBUTION OF CAPSULAR VIRULENT ANTIGENS - BHAVANI PRIYA S.,; PREMKUMAR A.,; SEKAR B.,; SEKAR T,; SUNDRAN .B, (International Journal of Pharma and Bio Sciences, 2016)
Methicillin resistant Staphylococcus aureus (MRSA) infection is a frequently encountered problem in pyogenic infections. There are different types of phenotypic methods to differentiate MRSA from MSSA with different specificity and sensitivity. However molecular detection of MRSA targeting mecA gene have been reported. Hence in the present study the detection of MRSA among the isolates of the S. aureus was carried out by both phenotypic and genotypic methods. Among the isolates of S. aureus the predominance of two capsular polysaccharides-types 5 and 8, was studied using PCR method. The detection rate of MRSA using HiCrome MeReSa Agar, Disk Diffusion test using oxacillin and cefoxitin and mecA gene using PCR was evaluated. The prevalence of MRSA was 35.5%(49/138) and 39.8%(55/138) of MSSA. Among clinical isolates 93% expressed either capsular polyssaccharide type 5 or type 8, whereas 6.7% were non-typeable. CP5 was predominantly found in 65.3% of MRSA strains, whereas CP8 were predominant among 61.8% of MSSA isolates.